Characterization of the complete chloroplast genome of longan (Dimocarpus longan Lour.) using illumina paired-end sequencing. Issue 2 (12th December 2017) - Wang, Kangyu; Li, Li; Zhao, Mingzhu; Li, Shaokun; Sun, Honghua; Lv, Yanxi; Wang, Yi
Abstract: Longan ( Dimocarpus longan Lour.), as a kind of commercial fruit tree in the family Sapindaceae, is widely cultivated in South Asia. In this study, we obtained the complete chloroplast genome sequence of longan using Illumina paired-end sequencing. It has 160, 833 bp in length, containing a pair of IR regions (28, 428 bp) separated by a small single-copy region (18, 270 bp) and a large single-copy region (85, 707 bp). The overall GC contents of the chloroplast genome were 37.8%. This circular genome contains 130 annotated genes, including 85 protein-coding genes, 37 tRNAs and 8 rRNAs. The phylogenetic analysis using maximum–likelihood (ML) and neighbour-joining (NJ) method showed that longan has the closest relationship with Litchi chinensis, Sapindus mukorossi and Dodonaea viscosa. This complete chloroplast genomes can be subsequently used for the genetic breeding of this valuable species.